PENERAPAN PRINSIP SOPAN SANTUN DALAM INTERAKSI BELAJAR MENGAJAR BAHASA INDONESIA DI KELAS VII SMP - Yogi Ardiansyah; Hary Soedarto Harjono; Rahmawati (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This research is motivated by the importance of the principle of politeness in sociallife, particularly within the school environment. Communication between studentsand teachers, as well as among students, takes place during the learning process.Therefore, the teaching and learning process taking place in the classroom must bebased on the principle of politeness. This study aims to describe the politenessprinciples applied in Indonesian language teaching and learning interactions in classVII A at SMP Negeri 14 Jambi City. This study employs a qualitative researchmethod and a descriptive research approach. The researcher employs this methodbecause the descriptive method focuses on understanding phenomena related tothe research topic. The data collection method in this study is observation using thelistening method. The data obtained were subsequently analyzed using thematching technique. The use of this method is based on the assumption that thelanguage being learned has a relationship with elements outside the language itself.The data analysis process involved recording the obtained data, identifying andclassifying the data, analyzing the data using pragmatic analysis, and drawingconclusions.